2004
DOI: 10.1136/jcp.2003.013094
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and relevance of EBV latency in nasopharyngeal carcinoma in Israel

Abstract: Background: Nasopharyngeal carcinoma (NPC) is frequently associated with Epstein-Barr virus (EBV). The incidence of NPC in Western countries is lower than in the Far East, and EBV latency in NPC is less prevalent. Israel, as a part of the Mediterranean area, is one of the countries with an intermediate risk for NPC. Methods: Immunohistochemistry (IHC) for latent membrane protein 1 (LMP-1) and in situ hybridisation (ISH) for EBV encoded RNA (EBER) were used to evaluate the prevalence and possible prognostic val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 14 publications
2
22
0
2
Order By: Relevance
“…We also found that all three histological types of NPC were associated with the presence of EBV. Our results are consistent with previous reports which suggest that NPC in the Mediterranean basin resembles the Asian type and is strictly associated with the EBV infection [2,13,40].…”
Section: Discussionsupporting
confidence: 83%
“…We also found that all three histological types of NPC were associated with the presence of EBV. Our results are consistent with previous reports which suggest that NPC in the Mediterranean basin resembles the Asian type and is strictly associated with the EBV infection [2,13,40].…”
Section: Discussionsupporting
confidence: 83%
“…Out of 35 cases of lymphoepithelial carcinoma10 cases were found in the younger age group(10-20 )yrs and 8 cases in the older age group(61-80) yrs,Balakrishnan et al 6 observed bimodal age distribution with peaks in age group (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and (45-54) yrs from India.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on normal nasopharyngeal tissue and premalignant biopsies indicated that genetic events occur early in the pathogenesis of NPC and they may predispose to subsequent EBV Downregulation of expression of transporters associated with antigen processing 1 and 2 and human leukocyte antigen I and its effect on immunity in nasopharyngeal carcinoma patients infection. The EBV latent-gene expression in NPC is predominantly restricted to the Epstein-Barr nuclear antigen 1, the latent membrane proteins (LMP) 2A and 2B and the BamHI-A transcripts, with approximately 70% of the tumors also expressing the oncogenic LMP1 protein (9)(10)(11). Currently, research is focused on the mechanisms underlying the escape of NPC from EBV-specific immune destruction and the development of novel strategies for immune intervention.…”
Section: Introductionmentioning
confidence: 99%